PPARalpha activators may be good candidates as antiaging agents - Erol, Adnan (Medical hypotheses, 2005)
Aging is associated with a metabolic decline characterized by the development of changes in fat distribution, obesity, and insulin resistance. Dysfunctional humoral and cell-mediated immune responses occur with age, and these aberrations have been implicated in the increased incidence of infectious diseases, hyporesponsiveness to vaccination, and the etiology of numerous chronic degenerative diseases. All these metabolic and immune alterations are associated with a variety of age-related diseases that subsequently result in increased mortality. Leptin can modulate many of the metabolic alterations characteristic of aging. Leptin resistance has been implicated in the pathogenesis of obesity-related complications involving abnormalities of lipid metabolism that resemble those of old age. Increased plasma leptin levels with aging suggest resistance to leptin action and may explain why elderly subjects have abdominal obesity and insulin resistance. Leptin's failure may be considered for the metabolic decline seen with aging. Peroxisome proliferator-activated receptor (PPAR)-alpha, the transcription factor for the mitochondrial and peroxisomal enzymes of beta-oxidation, and its target enzymes, are upregulated by hyperleptinemia. PPARalpha has been shown to mediate the action of the hypolipidemic drugs of the fibrate class on lipid and lipoprotein metabolism. PPARalpha activators furthermore improve glucose homeostasis and influence body weight and energy homeostasis. The administration of agents capable of activating the PPARalpha was found to restore the cellular redox balance, evidenced by a lowering of tissue lipid peroxidation, an elimination of constitutively active NF-kappaB, loss in spontaneous inflammatory cytokine production, and ailing in the aging immunity.